Bring on the weekend - Improving the quality of junior doctor weekend handover. Issue 2 (8th January 2014) - Jardine, Alan George Mackenzie; Page, Tristan; Bethune, Rob; Mourant, Philippa; Deol, Priya; Bowden, Caitlin; Dahill, Mark; Mische, Claudia; Cornish, Naomi; Sanders, Victoria; Lee, Joanne; Bethune, Rob
Abstract: While it is widely recognised that communication and handover are a fundamental component in providing safe clinical care for hospital patients (1, 2.3). The Royal College of Physicians found that the majority of hospital doctors are dissatisfied with the standard of their handovers (4). These findings were mirrored by the junior staff at the Royal United Hospital, who felt that the weekend handover was inadequate, and detrimental to patient safety. A group of eight junior doctors at the Royal United Hospital, Bath utilised The Model For Improvement to systematically analyse and improve various aspects of the weekend handover system. Handover sheets from a subset of wards were assessed to observe direct effects of staged interventions over a nine month period, allowing small-scale testing prior to widespread implementation of a standardised intranet-based weekend handover. The effects of interventions were evaluated using a predesigned scoring system and data was collected continuously throughout the project. Over a nine month period the quality of handovers improved significantly from 76% to 93% (p <0.01): a success which was supported by a 100% improvement in formal feedback collected from hospital doctors and highlighted by the desire of senior staff and directors to implement the system throughout the trust. Using The Model For Improvement a group of junior doctors were able to introduce and develop a standardised weekend handover system that met their requirements. A structured, efficient and auditable system has been successfully produced which improves the quality and safety of patient care.